Pictorial essay: Salivary gland imaging - Rastogi, Rajul; Bhargava, Sumeet; Mallarajapatna, Govindarajan Janardan; Singh, Sudhir Kumar (Indian Journal of Radiology and Imaging, 2012)
Salivary glands are the first organs of digestion secreting their digestive juices into the oral cavity. Parotid, submandibular, and sublingual glands are the major paired salivary glands in the decreasing order of their size. In addition, multiple small minor salivary glands are noted randomly distributed in the upper aerodigestive tract, including paranasal sinuses and parapharyngeal spaces. The imaging is directed to the major salivary glands. Commonly used imaging methods include plain radiography and conventional sialography. Recently, high-resolution ultrasonography (HRUS) is being increasingly used for targeted salivary gland imaging. However, the advent of cross-sectional imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) have revolutionized the imaging of salivary glands. This article illustrates the role of imaging in evaluating the variegated disease pattern of the major salivary glands.
Keywords: Computed tomography; imaging; magnetic resonance imaging; salivary glands